Criminal Acts of Sexual Violence Against Women That Occurred in The Southeast of The Kei Islands of Maluku, Maluku Province - Miftahul Jannah Raubun; Siti Miskiah (International Journal Labs, 2025)
The crime of sexual violence against women in Southeast Maluku Regency, Maluku Province, is a serious problem that has a wide impact on victims, families, and communities. This study aims to identify the types of sexual violence that often occur, the causative factors, the effectiveness of legal protection for victims, and a review of Islamic law against this crime. The method used in this study is a juridical-sociological approach with positive legal analysis and Islamic law. Result Research shows that the dominant forms of sexual violence in this region include verbal and physical sexual harassment, rape, sexual exploitation, which contains sexual elements. The main causative factors include a strong patriarchal culture, low legal awareness of the community, social stigma against victims, and weak law enforcement. Although Indonesia has regulations such as Law Number 12 of 2022 concerning the Crime of Sexual Violence (TPKS Law), implementation in Southeast Maluku still faces various obstacles, including a lack of resources for law enforcement and victim rehabilitation. From the perspective of Islamic law, sexual violence is categorized as a serious offense that can be punished with hudud, qisas, or ta'zir, depending on the level of the crime committed. Islam also emphasizes the principle of protection of women's honor and safety. Therefore, a more comprehensive approach is needed through strengthening law enforcement, increasing public awareness, and integrating positive law with Islamic values to ensure maximum protection for victims of sexual violence.